B cells produce less IL-10, IL-6 and TNF-alpha in myasthenia gravis - DİRESKENELİ, RAFİ HANER (TAYLOR & FRANCIS LTD, 2015)
B cells from myasthenia gravis (MG) patients with autoantibodies (Aab) against acetylcholine receptor (AChR), muscle-specific kinase (MuSK) or with no detectable Aab were investigated as cytokine producing cells in this study. B cells were evaluated for memory phenotypes and expressions of IL-10, IL-6 and IL-12A. Induced productions of IL-10, IL-6, IL-12p40, TNF-alpha and LT from isolated B cells in vitro were measured by immunoassays. MG patients receiving immunosuppressive treatment had higher proportions of memory B cells compared with healthy controls and untreated patients. With CD40 stimulation MG patients produced significantly lower levels of IL-10, IL-6. With CD40 and B cell receptor stimulation of B cells, TNF-alpha production also decreased in addition to these cytokines. The lower levels of these cytokine productions were not related to treatment. Our results confirm a disturbance of B cell subpopulations in MG subgroups on immunosuppressive treatment. B cell derived IL-10, IL-6 and TNF-alpha are down-regulated in MG, irrespective of different antibody productions. Ineffective cytokine production by B cells may be a susceptibility factor in dysregulation of autoimmune Aab production.
Keywords: Autoantibody; B cell; cytokine; myasthenia gravis; BLOOD MONONUCLEAR-CELLS; MESSENGER-RNA EXPRESSION; REACTIVE T-CELLS; MULTIPLE-SCLEROSIS; RECEPTOR; CYTOKINES; SUBPOPULATIONS; AUTOIMMUNITY; ACTIVATION; ANTIBODIES